Chapter 1 - An overview of the potential applications based on HPP mechanism - Ghafoor, Kashif; Gavahian, Mohsen; Marszałek, Krystian; Barba, Francisco J.; Xia, Qiang; Denoya, Gabriela Inés (Elsevier, 2020)
Over the last decades, high-pressure processing (HPP) has shown its potential as one of the most relevant technologies for nonthermal food processing mainly due to its application for microbial inactivation while retaining fresh-like characteristics of the food. Moreover, HPP can be considered as a potential tool for developing new food products with new sensorial and functional properties. Apart from food preservation, the application of HPP to improve health attributes (e.g., reducing food contaminants or salt concentration), and to enhance the extraction or fermentation processes, has been an interesting research topic around the world. This chapter intends to show the core-base processing characteristics of HPP, highlight the advantages and limitations of this nonthermal processing, and discuss the potential applications of HPP in the food industry.